EFFECTIVENESS OF OBJECTION INSTITUTIONS IN RESOLVING TAX DISPUTES - Sitorus, Roslima; Ratna Mulyaningrum, Edith (Jurnal Meta-Yuridis, 2024)
Taxes have an important role in state revenue, but tax disputes often arise between taxpayers and the Direktorat Jendral Pajak (DJP). The dispute resolution mechanism through the objection institution regulated in the legislation faces challenges related to independence and effectiveness. This study uses a normative juridical method with a descriptive approach to analyze the mechanism and effectiveness of objection institutions in handling tax disputes. The results of the study show that although the objection procedure has been established, most of the objection applications are rejected, this raises doubts about the independence of the institution due to the inequality of position between the taxpayer and the DJP which affects the effectiveness of the objection institution. The conclusion of this study emphasizes the need for reforms to increase transparency and fairness in the objection process to be more effective in resolving tax disputes.